1993
DOI: 10.1182/blood.v82.4.1192.1192
|View full text |Cite
|
Sign up to set email alerts
|

Complement-induced vesiculation and exposure of membrane prothrombinase sites in platelets of paroxysmal nocturnal hemoglobinuria

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired stem-cell disorder in which the glycolipid-anchored membrane proteins, including the cell-surface complement inhibitors, CD55 and CD59, are partially or completely deleted from the plasma membranes of mature blood cells. To gain insight into the pathogenesis of thrombosis that is frequently observed in this disorder, the procoagulant responses of PNH platelets exposed to the human terminal complement proteins C5b-9 were investigated. C5b-9 complexes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(70 citation statements)
references
References 26 publications
1
64
0
4
Order By: Relevance
“…In addition, changes in stimulus-response coupling have been reported in response to purified complement components, with protein kinase C activation followed by influx of calcium. C5b-9 assembly on the platelet was also found to induce granule secretion, thromboxane synthesis and assembly of the prothrombinase complex (Wiedmer et al, 1987(Wiedmer et al, , 1993. However, it is of note that aggregation of platelets did not appear to occur in any of these studies using purified complement, despite the signalling events which were stimulated, suggesting that complement alone may be insufficient to induce irreversible aggregation but it may enhance the response (Polley & Nachman, 1978;Polley et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes in stimulus-response coupling have been reported in response to purified complement components, with protein kinase C activation followed by influx of calcium. C5b-9 assembly on the platelet was also found to induce granule secretion, thromboxane synthesis and assembly of the prothrombinase complex (Wiedmer et al, 1987(Wiedmer et al, , 1993. However, it is of note that aggregation of platelets did not appear to occur in any of these studies using purified complement, despite the signalling events which were stimulated, suggesting that complement alone may be insufficient to induce irreversible aggregation but it may enhance the response (Polley & Nachman, 1978;Polley et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence, however, for stimulation of platelets or modulation of platelet activation by the terminal complement complex, C5b-9. Wiedmer et al (1987Wiedmer et al ( , 1993 showed that when purified complement components were assembled on the platelet surface, there was an influx of Na 2+ ions with concomitant depolarization of the membrane, rapidly followed by repolarization which apparently prevents platelet lysis. In addition, changes in stimulus-response coupling have been reported in response to purified complement components, with protein kinase C activation followed by influx of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…As blocking CD59 on normal platelets enhances these procoagulant responses [51], a similar response to MAC assembly would be expected in GPI-deficient PNH platelets. In vitro studies by Wiedmer et al [52] showed that PNH platelets did indeed expose more FVa-binding sites and increased thrombin generation more than normal platelets upon MAC stimulation. Ex vivo studies provided some evidence for in vivo platelet activation [24], but these findings were not confirmed by others [43,53].…”
Section: Platelet Functionmentioning
confidence: 99%
“…Other potential mechanisms have been reported in PNH (Weidmer et al, 1993;Gralnick et al, 1995;Ross & Ware, 1995), one being the lack of the complement inhibitor CD59 from the platelet surface. Absence of this protein makes the platelet susceptible to terminal complement protein C5b-9 (membrane attack complex, MAC)induced injury and activation may contribute to the thrombotic tendency in PNH (Weidmer et al, 1993). Measuring populations of platelets deficient in GPI-linked proteins by flow cytometry is a sensitive method of studying the relationship between these proteins and thrombosis.…”
Section: Discussionmentioning
confidence: 96%
“…This hypercoagulable state is partially related to the deficiency from the platelet surface of GPI-linked complement inhibitors such as CD59. Absence of this protein makes the platelet susceptible to terminal complement protein C5b-9-induced injury, and activation may contribute to the thrombotic tendency in PNH (Weidmer et al, 1993). Measurement of GPI-linked protein-deficient populations of platelets would therefore be important for studying the relationship with thrombosis.…”
mentioning
confidence: 99%